2005
DOI: 10.1074/jbc.m412105200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Mismatch Repair-dependent Response to Fluoropyrimidine-generated Damage

Abstract: Previous studies from our laboratory indicated that expression of the MLH1 DNA mismatch repair (MMR) gene was necessary to restore cytotoxicity and an efficient G 2 arrest in HCT116 human colon cancer cells, as well as Mlh1 ؊/؊ murine embryonic fibroblasts, after treatment with 5-fluoro-2-deoxyuridine (FdUrd). Here, we show that an identical phenomenon occurred when expression of MSH2, the other major MMR gene, was restored in HEC59 human endometrial carcinoma cells or was present in adenovirus E1A-immortalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 58 publications
12
113
1
1
Order By: Relevance
“…Arrest in G2 is observed within the first cell cycle in MMR-proficient cells, but not in MMR-deficient cells (Carethers et al, 1999;Meyers et al, 2003Meyers et al, , 2005. Inhibition of TS without FU treatment elicits a G2 arrest regardless of MMR status suggesting that the contribution of MMR to DNA damage signalling is via incorporation of FPs into DNA as opposed to the inhibition of TS and the resulting imbalance in nucleotide pools.…”
Section: Mmr and Dna Damage Signallingmentioning
confidence: 95%
See 1 more Smart Citation
“…Arrest in G2 is observed within the first cell cycle in MMR-proficient cells, but not in MMR-deficient cells (Carethers et al, 1999;Meyers et al, 2003Meyers et al, , 2005. Inhibition of TS without FU treatment elicits a G2 arrest regardless of MMR status suggesting that the contribution of MMR to DNA damage signalling is via incorporation of FPs into DNA as opposed to the inhibition of TS and the resulting imbalance in nucleotide pools.…”
Section: Mmr and Dna Damage Signallingmentioning
confidence: 95%
“…For example, Pani et al (2007) have shown that the MMR pathway contributes to the cytoxicity of cisplatin in human cells; however, other pathways are also critical in mediating the response to cisplatin particularly homologous recombination. In the case of FdU, widely used as an adjuvant therapy in advanced colorectal cancer, MMR-mediated apoptosis (Meyers et al, 2005) may be one of several contributors to the overall cytotoxicity of FdU as base excision repair (BER) enzymes also target FdU (Meyers et al, 2004). The BER enzyme SMUG1 removes FdU from DNA and confers protection from cell killing .…”
Section: Mmr and Dna Damage Signallingmentioning
confidence: 99%
“…Base excision repair of individual misincorporated nucleotides would probably not generate an effective Chk1-activating signal, since it is unlikely to create significant tracts of single-stranded DNA (Zou and Elledge, 2003). However, processing and repair of DSBs, which are thought to arise as a consequence of simultaneous BER of multiple, closely spaced lesions in 5FU-treated cells (Ingraham et al, 1986), likely would suffice, as might longer single-strand repair tracts arising from MMR-mediated excision of individual misincorporations of FdUTP (Meyers et al, 2005). We further speculate that the purpose of Chk1-dependent S-phase slowing may be to limit the accumulation of misincorporated FdUTP/dUTP under conditions of nucleotide pool perturbation by allowing time for multiple cycles of excision, re-synthesis, and repair at individual replication forks.…”
Section: Chk1 Protects Tumour Cells Against Killing By 5fumentioning
confidence: 99%
“…Fluorodeoxyuridine monophosphate is also converted into fluorodeoxyuridine triphosphate (FdUTP) which itself is a substrate for DNA polymerases and readily misincorporated into DNA (Sampath et al, 2003). FdUTP or dUTP misincorporation is potentially mutagenic and miscoding, however, both can be excised through the action of base excision repair (BER) (Ingraham et al, 1980;Mauro et al, 1993) and, in the case of FdUTP, potentially mismatch repair (MMR) (Meyers et al, 2001(Meyers et al, , 2005Tajima et al, 2004). Finally, conversion of 5FU to fluorouridine triphosphate allows incorporation into both messenger and structural RNAs with potentially deleterious effects on stability, processing, modification, and coding potential (Longley et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Defects in MMR proteins have been found be associated with reduced or absent benefit from 5-FU adjuvant chemotherapy in clinical trials (Ribic et al, 2003). MMR impairment appears to cause reduced incorporation of 5-FU metabolites into DNA, leading to reduced G2/M arrest and apoptosis after 5-FU treatment (Meyers et al, 2005;Hewish et al, 2010). The deficiencies of MMR genes are also associated with MNNG, 6-thioguanine and cisplatin (Fiumicino et al, 2000;Meyers et al, 2001;Loo et al, 2005).…”
Section: Aberrant Dna Methylation and Epigenetic Inactivation Of Hmshmentioning
confidence: 99%